Harmonization of the order payment procedure. The European order for payment procedure as a starting point - Alba Cladera, Felip (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper questions whether it makes sense that the European order for payment procedure continues to limit its scope to cross-border cases. The analysis of the points of convergence and divergence between the European order for payment procedure and other national orders for payment procedures —particularly the Spanish— shows that the European order for payment procedure might constitute the basis for a harmonization of the order for payment procedure at European level. At the same time, and taking into account that harmonization requires the most perfect legislation possible, proposals are made to solve some deficiencies that have been detected in the application of the European order for payment procedure.
Keywords: European Civil Procedural Law; European order for payment; harmonisation; scope; service; ex officio control of unfair terms